The rights of persons with disabilities in international law and its reflection on the laws of Iraq and the Kurdistan Region - يوسف, د. بەفراو رؤوف حمه; محمد, جیهاد كريم; عثمان, گولستان احمد; عبدالله, بورهان احمد; مجید, کوردە باپیر (Sulaimani Journal for Humanities, 2025)
A person with a disability is an undesirable situation that any human being may experience during their lifetime; Persons with disabilities want their basic rights and cannot achieve their real rights except through special assistance and protection. In this regard, the United Nations has been protecting the rights of persons with disabilities since This study attempts to examine the legal and social implications of Iraq's accession to the Convention on the Rights of Persons with Disabilities and its ratification in 2012. By interpreting the rights of persons with disabilities in the Kurdistan Region their existence? What are the problems and obstacles to achieving their full rights? The research hypothesis is that contrary to the many laws in the field of adaptation requirements, there is negligence in the implementation of the duties of the relevant institutions in this area and people with disabilities have not fully achieved their rights. The research in this study is practical in its aim and its content was obtained by review method using translated books and research articles.
Keywords: People with disabilities; rights; international conventions; national laws; social welfare; Kurdistan Region; implementation guarantees